The African Gender and Development Index: an engendered and culturally sensitive statistical tool - Charmes, Jacques; Wieringa, Saskia E.; Ruzvidzo, Thokozile; Rosalie, Gonzaque (Frontiers in Sociology, 2023)
In 2004 the African Union adopted an innovative gender index, the Afriacn Gender and Development Index (AGDI). It is composed of the quantitative Gender Status Index (GSI) and the qualitative African Women's Progress Scorecard (AWPS). The tool is built on the use of national data collected by a national team of specialists. Since the beginning three cycles of implementation have occurred. After the last cycle the AGDI was revised. In this article the authors assess the implementation of the AGDI, against the background of other gender indices, and discuss the latest revisions